PROFIL PEMECAHAN MASALAH PADA MATERI PERSAMAAN LINIER SATU VARIABEL DENGAN MENGGUNAKAN PENDEKATAN MODEL ELICITING ACTIVITIES (MEAs) DILIHAT DARI KEMAMPUAN MATEMATIKA - Rahayuningrum1, Anita; Setyawan, Fariz; Khasanah, Uswatun (AlphaMath : Journal of Mathematics Education, 2018)
The purpose of this study is to know the problem-solving profile in Linear Equation of One Variable (LEOV) by using Model Eliciting Activities (MEAs) based on the student’s mathematics ability. This study is a descriptive qualitative research. The subjects of the study are chosen by using purposive sampling and 7th grade junior high school students are selected as the sample of the research. Furthermore, the data is classified into two categories, there are the students with high and low mathematics ability categories. The data was analyzed and described as the mathematics problem-solving profile based on Polya’s four steps method. The result of the study shown that the subject with high mathematics ability solved the problem using all the Polya’s four steps method. The initial step derived by the subjects were understanding the problem. Next, the subjects wrote the given information, the question, and the missing data while they were solving the problem. In the carrying out the plan, the students perform any necessary actions such as formulating, modelling and computations. The problem was well-formulated by using appropriate steps and well-described in each procedure. The computation derived by the subject was examined after conclusion. The appropriate computation derived by the subject attains well-outcomes. The obtained numbers are well described in each step of solving the given problem. It implies that the indicator of problem-solving were achieved based on the given description. However, the subjects with low categories were lack to describe the devising strategy while solving the given problems.